Study on evaluation of gamma oryzanol of germinated brown rice by near infrared spectroscopy - Kannapot Kaewsorn; Panmanas Sirisomboon (My University, 2013)
Germinated brown rice (GBR) is rich in gamma oryzanol which increase its consumption popularity, particularly in the health food market. The objective of this research was to apply the near infrared spectroscopy (NIRS) for evaluation of gamma oryzanol of the germinated brown rice. The germinated brown rice samples were prepared from germinated rough rice (soaked for 24 and 48 h, incubated for 0, 6, 12, 18, 24, 30 and 36 h) and purchased from local supermarkets. The germinated brown rice samples were subjected to NIR scanning before the evaluation of gamma oryzanol by using partial extraction methodology. The prediction model was established by partial least square regression (PLSR) and validated by full cross validation method. The NIRS model established from various varieties of germinated brown rice bought from different markets by first derivatives+vector normalization pretreated spectra showed the optimal prediction with the correlation of determination (R 2 ), root mean squared error of cross validation (RMSECV) and bias of 0.934, 8.84 × 10 -5 mg/100 g dry matter and 1.06 × 10 -5 mg/100 g dry matter, respectively. This is the first report on the application of NIRS in the evaluation of gamma oryzanol of the germinated brown rice. This information is very useful to the germinated brown rice production factory and consumers.
Keywords: Brown rice; Spectroscopy and Chemometric Analyses